Experimental method to determine the pore structure and pore size distribution of gamma alumina (-Al2O3) material - Thai, Vu Hong (Vietnam Journal of Chemistry, 2017)
Gamma Alumina (g-Al2O3) is a material with many good properties such as small pore size, high specific surface area, highly hygroscopic, and low melting temperature. These characteristics are very suitable for making adsorbent and catalyst carriers. Gamma alumina is widely applied in many industries such as petrochemical industry, chemical industry, and pharmaceutical industry. Therefore, the identification of the characteristics of the Gamma Alumina material is very important and helpful. In this research, experiments will be carried out to determine the pore structure, the pore size distribution of γ-Al2O3 particles. Modern and appropriate experimental methods are applied. Descriptions of the experimental methods and equipment are given. The first experiment is the pore structure determination of the material by using environmental scanning electron microscopy (ESEM). The second one is the pore size distribution determination with the help of Hg-porosimetry method. Experimental results will be presented and discussed. Keywords. Pore structure, pore size distribution, gamma alumina